If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 6 + 32 = 53 Reorder the terms: 6 + 32 + 3x = 53 Combine like terms: 6 + 32 = 38 38 + 3x = 53 Solving 38 + 3x = 53 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-38' to each side of the equation. 38 + -38 + 3x = 53 + -38 Combine like terms: 38 + -38 = 0 0 + 3x = 53 + -38 3x = 53 + -38 Combine like terms: 53 + -38 = 15 3x = 15 Divide each side by '3'. x = 5 Simplifying x = 5
| e^5x-6=76 | | 11y+5=-5+6y | | -2(-2f-3)=2(4f-7) | | .2+4=1.2x+8.0 | | 20x+30=4 | | 12=2(3n+1)-8(5n+3) | | 4y-9(3y-2)= | | Y=-.01x^2+.5x+3 | | 32+6x=53 | | 118-3.8t=7.36-1.9t | | (16x-6)=180 | | .26(2.39x-4.91)=10.64 | | 6x+9x+x=180 | | -2x-4(7x-2)=-6x+8 | | 0.125(6+n)=2.50 | | 25x^5+10x^4-20x= | | sqrt(15x)=3x | | 7p-(-3p)+(-5)=15 | | 6x+32=53 | | 0=-16t^2+368 | | -4x-27=7 | | 25x^5+10x^4-20= | | =19-16(-9+17k) | | 3x+8=-3+4c | | 2l-4s=50 | | (x^2)(p^2)+xyp-6y^2=0 | | 1-4p=y | | X^2+2x-9=180 | | 10x^2+14x= | | 10a-7+9=26 | | (5x+30)=7x | | T^2+14T-40=0 |